The Reduction of Carbohydrate, Fat and The Increment of Protein Content of Some Nigerian Diets by Traditional Fermentation - Ehoche E Elijah; Henry Y Adeyemi (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2018)
Fermentation is vital to African food processing. Its effects on the percentage carbohydrate, proteins, lipid and moisture composition of laboratory prototypes of the fermented seed from Parkia biglobosa, (Dawadawa) condiment paste, fermented milk (Nono), corn (Zea mays)-based pap (Akamu), soybean (Glycine max) based-cheese paste (wara) and soy-milk (soymilk). The major macro-nutrient and moisture contents of each food product and their respective substrates were determined using standard methods and compared. The result showed that there was a noticeable fall in the carbohydrate content in the Corn (56.23±9.09 %) as it was converted to Akamu (7 .63±2.67 %) just as was noticed in the fermentation of Nono (11.99±2.67 %) from fresh cow milk (42.3±1.60 %). The similar trend was also found in the fermentation of the lipid-containing soy bean seed (41±7) to soy wara (7.6±2 %) and soymilk (5.6±2.2 %). However, there was an increase in the protein content from the fermentation of Parkia biglobosa seed: 31.62±0.83 - 34.17±3.6 % in Dawadawa and 25.25±0.59 - 37.74±1.8 % in Nono. Moisture contents of the various fermented food products also increased as follows: from 9.00 ±0.01-90.0±0.70 in Akamu; 89.0±0.58 into 92.7±0.98 in Nono, 13.0±0.87 -33±0.01 in Dawadawa paste, and 5.0±0.01 - 39±1.41 % in soy milk and 31 ±1.4 % in soy wara. These show that fermenting foods could reduce their carbohydrate and fat content relatively but increase their protein content. These cannot be overemphasized considering the problem of malnutrition which is prevalent around this part of the world.